THE ASSESSMENT OF TAMARIX APHYLLA AND CALOTROPIS PROCERA COMPARATIVE AND COMBINE ANTIOXIDANT POTENTIAL - Shahid Khan; Khan, Dr. Fahim Ullah; Saira Abbas; Mir Sadiq Shah; Autif Hussain Mangi; Shahid Ullah; Abdu Razzaq Khan; Shahid Iqbal; Batab Khan; Surayia Shahab Rani (LIAQUAT MEDICAL RESEARCH JOURNAL, 2023)
Free radicals alter DNA, resulting in various chronic disorders, including cancer. Herbal therapy has a significant potential to block cancer progression and other chronic diseases. The Tamarix aphylla plays an essential role in the modulation of free radicals. Calotropis procera (leaves), a tropical medicinal plant, has shown protective effects against cancer progression. We have examined the antioxidant therapy of separate or combined forms of the Tamarix aphylla and Calotropis procera plant extracts. Tamarix aphylla demonstrated scavenging activity at various concentrations, including 100 microgram/ml, 500 microgram/ml, and 1000 microgram/ml (29%, 37% and 62%). The scavenging activity of Calotropis procera at various concentrations (100 microgram/ml, 500 microgram/ml, and 1000 microgram/ml) was 20%, 31% and 40% against the standard of ascorbic acid (65%, 77% and 84%). The mixture of both plant extracts displayed significant antioxidant potential at various concentrations 100 microgram/ml, 500 microgram/ml, and 1000 microgram/ml which were 45%, 64% and 78%. Our study showed that the mixture of both plants has a significant antioxidant potential by comparing individual plant extracts. Further studies are recommended to elucidate the anti-cancer potential of both plant extracts mixture using in vivo approach for tumor models.